Selected antecedents, attitudes and willingness to purchase counterfeit sportswear products by students at a selected higher education institution - Mahlangu, Selinah Makamoho (Vaal University of Technology, 2021)
Counterfeiting is a global phenomenon in developed and developing countries, causing a threat to national economies and societies. It negatively harms new investment and progressively endangers public health and safety as well. Known and famous brands are often targeted for counterfeiting. This phenomenon is primarily driven by consumers’ aspiring attitudes, social media pressures and the need to differentiate oneself. The aim of the study is to examine the influence of materialism, hedonic consumption motive, utilitarian consumption motive, personal gratification and novelty-seeking on attitudes and the influence of attitudes on willingness to purchase counterfeit sportswear products at a selected HEI. The study is grounded within the positivist philosophy, in which a quantitative research approach was followed, since positivists prefer an analytic and factual interpretation of quantitative data. An online structured questionnaire was used to collect data through an online survey. The study sample was conveniently selected from a population of registered students at a selected HEI in Southern Gauteng in the 2020 academic year. Data were collected on demographic variables, materialism (MAT), hedonic motivation (HED), utilitarian motive (UTL), personal gratification (PGT), novelty-seeking (NOS), attitude towards counterfeits (ATC) and willingness to purchase (WTP) counterfeit sportswear. A total of 327 questionnaires were completed and used in the final data analysis. Descriptive statistics techniques, correlations and regression analysis were used to evaluate perceptions and relationships between the study constructs. The research results revealed the existence of significant positive associations amongst the study constructs. Of the five antecedents, two of the five predictor variables, namely, UTL and NOS showed significant predictive relationships with attitudes towards counterfeit sportswear purchases. Attitudes towards counterfeits (ATC) also emerged as a significant predictor of students’ WTP counterfeit sportswear. Since NOS and UTL seem to predict a positive attitude towards counterfeit sportswear, the study recommends that brand owners develop awareness about ethical purchasing behaviour. They should also educate consumers on the social and economic downside of buying counterfeit products and that seeking novelty when purchasing counterfeit products may soon wane and wear off, leading to regret and cognitive dissonance. Further, brand marketers should also emphasise the utility value inherent in the purchase of authentic branded products instead of buying counterfeits. Since consumers cannot often readily distinguish between genuine and fake sportswear, it is therefore critical for marketers of branded products to promote the contrast of originals and fakes and to underline the quality, longevity, and dependability of their authentic products in the market. These results make a valuable contribution to academics, brand managers and marketers, as the results reveal that consumer buying can be influenced by personality and social interests of different individuals. The study notes that laws only cannot prohibit the sale and purchase of counterfeit products. It requires the stricter implementation thereof. Further, there is a need for behavioural change strategies to counter the effects of counterfeiting. Nudges such as promotions and loyalty programmes may encourage the purchase of authentic products as opposed to the purchase of counterfeits.
M. Tech. (Department of Marketing, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Counterfeit; Intellectual property rights; Sportswear; Theory of planned behaviour; HEI; Materialism; Hedonic; Utilitarian; Novelty-seeking; Personal gratification; Attitudes; Behaviour; Dissertations, Academic -- South Africa.; Branding (Marketing).; Product counterfeiting.; Consumer behavior.